2004
DOI: 10.1007/s00432-003-0525-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of telomerase activity in prostate massage samples improves differentiating prostate cancer from benign prostatic hyperplasia

Abstract: Our data indicate that telomerase activity detected by TRAP assay on prostate epithelial cells collected by prostate massage can substantially improve the distinction between Pca and BPH conditions. One of the clinical benefits resulting from the use of this new assay would be to refine the biopsy indication and to avoid for several patients without Pca the unnecessary cost and the complications of prostate biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
0
21
1
Order By: Relevance
“…Because tumor cells may be present in low numbers and because the enzymatic activity of telomerase and the PCR efficiency might be affected by the presence of inhibitors in urine, we combined the standardized sample processing with highly sensitive measurements of telomerase activity by quantitative real-time PCR. In contrast to previously published studies (35,41,42) that have reported telomerase activity in exfoliated cells in prostatic fluid and urine in 90%, 91%, and 58% of prostate cancer patients, respectively, in the present study, all patients with clinically localized prostate cancer have shown relatively high levels of telomerase activity that corresponds to 100% of the assay sensitivity. These data are in agreement with basic knowledge that tumor cells exfoliate early during carcinogenesis, before the primary tumor can be detected by standard clinical tests (CAP Today Archive, July 1998).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Because tumor cells may be present in low numbers and because the enzymatic activity of telomerase and the PCR efficiency might be affected by the presence of inhibitors in urine, we combined the standardized sample processing with highly sensitive measurements of telomerase activity by quantitative real-time PCR. In contrast to previously published studies (35,41,42) that have reported telomerase activity in exfoliated cells in prostatic fluid and urine in 90%, 91%, and 58% of prostate cancer patients, respectively, in the present study, all patients with clinically localized prostate cancer have shown relatively high levels of telomerase activity that corresponds to 100% of the assay sensitivity. These data are in agreement with basic knowledge that tumor cells exfoliate early during carcinogenesis, before the primary tumor can be detected by standard clinical tests (CAP Today Archive, July 1998).…”
Section: Discussioncontrasting
confidence: 99%
“…Our study had principal differences with similar recently published studies (35,41,42). First, we collected post-prostatic massage exfoliated cells prospectively, without prior knowledge of clinicopathologic data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue samples were cultured in DMEM as previously described (31)(32)(33). Cultured cells were analysed for the presence of AR, EGFR, prostate-specific antigen (PSA) and telomerase activity, TRAP (34).…”
Section: Methodsmentioning
confidence: 99%
“…Several groups have measured telomerase activity with the telomeric repeat amplification protocol assay and obtained sensitivities of 58, 90 and 100% and specificities of 100, 87 and 89%, respectively. [25][26][27] Meid et al 25 also found a significant association between Gleason score and telomerase The abbreviation is not standing for official gene symbol approved by the HUGO Gene Nomenclature Committee.…”
Section: Advantages and Limitations Of Novel Urine Markersmentioning
confidence: 99%